THE STUDY OF THE SPATIO-TEMPORAL ORIENTATION ABILITY OF STUDENTS PRACTICING SPORTS DANCE AT THE UNIVERSITY OF BUCHAREST (University Arena, 2025)
Background. Sports dance is characterized by a complex coordination, its most important components being, in our opinion: the segmental, general and multisegmental coordination; the capacity of kinesthetic differentiation; the static and dynamic coordination, the ability of spatio-temporal orientation; the ability to perceive and reproduce musical rhythm and tempo. Sports dance lessons are held in the University of Bucharest with students who opt for this discipline without having a prior selection. In sports dance, all the motor capacities are involved in different weights, but we proposed for this study to analyze from the perspective of the coordinative capacities, the spatio-temporal orientation. Objectives. The subjects in this study are students in the 1st and 2nd years, belonging to different faculties of the university and they were divided into the control and the experimental groups. Both groups worked to test a salsa choreography during the lessons. In the experimental group, the choreography was practiced facing points 1,3,5,7, and in the control group, the choreography was practiced facing point 1. The test was realized with reference to point 5. Methods. The working methods used are observation, testing method, statistical-mathematical and graphical interpretation method. Results. The results were significantly better in the experimental group compared to the control group. The subjects in the experimental group were able to orient themselves better in space and time in a percentage of 85% and in the control group the percentage was about 30% Conclusion. We believe that the orientation in space and time can be improved by simple means, prepared by the teacher in the sports discipline, the methodological work being implemented according to the groups.
Keywords: spatio-temporal orientation; choreography; sports dance lesson; testing